2016
DOI: 10.18203/2319-2003.ijbcp20164756
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous drug reactions notified by ADR monitoring centre in a tertiary care hospital of Bihar

Abstract: Background: Cutaneous drug reactions are most frequent drug related adverse events which lead to early treatment discontinuations, high treatment cost and leading cause of morbidity and mortality. The aim of this study is to analyze the clinical patterns and offending drugs as well as their causality, severity and preventive strategies.Methods: All adverse drug reactions (ADRs) forms filled from May 2015 to April 2016 were scrutinized and forms with cutaneous drug reactions were analyzed and assessed for causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
2
1
0
Order By: Relevance
“…Variability observed in the severity of the reported cases across various studies could be due to difference in the clinical settings and the difference in speciality healthcare services provided by different hospitals. 25,37,38 It was observed that 8.62% of the reported cutaneous ADRs were probable preventable and the remaining 91.38% were not preventable and this is in accordance with a previous study. 37 As this is a retrospective analytical study, we could analyse the reactions and suspected medications as notified in the reporting form.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Variability observed in the severity of the reported cases across various studies could be due to difference in the clinical settings and the difference in speciality healthcare services provided by different hospitals. 25,37,38 It was observed that 8.62% of the reported cutaneous ADRs were probable preventable and the remaining 91.38% were not preventable and this is in accordance with a previous study. 37 As this is a retrospective analytical study, we could analyse the reactions and suspected medications as notified in the reporting form.…”
Section: Discussionsupporting
confidence: 91%
“…With the exception of palmar plantar erythrodysesthesia and acne, the occurrence of other cutaneous ADRs were in conformity with other studies. 10,22,24,25 The higher occurrence of palmar plantar erythrodysesthesias in the present study compared to other studies is due to cancer chemotherapy drugs used in medical oncology department of this institute. These variations observed among various studies could be due to different patterns of drug usage as per the scope and services of the respective hospitals.…”
Section: Discussionmentioning
confidence: 45%
“…[ 20 ] The result of the study by Manjhi et al ., 2017 showed that 88.12% ADRs were probable, 9.37% were classified as possible; 1.25 doubtful and 1.25% were definitely related to the drug as per Naranjo algorithm. [ 21 ] The outcomes are consistent with other studies utilizing Naranjo's assessment. Our results showed [ Table 4 ] that as per LCAT, 4.8% possible, 61.9% probable and 33.3% definite.…”
Section: Discussionsupporting
confidence: 88%